Moral Politics in the Philippines: Inequality, Democracy and the Urban Poor - Juliano, Hansley (Kasarinlan: Philippine Journal of Third World Studies, 2018)
Review of Moral Politics in the Philippines: Inequality, Democracy and the Urban Poor by Wataru Kusaka.